A ideia de insociável sociabilidade na filosofia da história de Immanuel Kant - Barros, Wagner Barbosa de (Universidade Federal de São Carlos, 2017)
The present dissertation aims to analyze three essays from the german philosopher Immanuel Kant that deal with his philosophy of history, highlighting within them the concept of unsociable sociability. The essays are: Idea for a Universal History from a Cosmopolitan Perspective, Conjectural Beginning of Human History and Toward Perpetual Peace. In our understanding, it is possible to assume the idea of antagonism as a guiding thread of an analysis of Kant's philosophy of history, insofar as it is shown that for the philosopher the unsociable sociability is the source of all human progress. Our objective is to highlight three historical philosophical moments in the analyzed texts, and to demonstrate how antagonism is responsible for the passage from one moment to another, thus, corroborating its importance.
Keywords: Sociabilidade; Insociabilidade; História; Direito; Kant, Immanuel, 1724-1804; Sociability; Insociability; History; Right; CIENCIAS HUMANAS::FILOSOFIA